The Diversity of Midgut Bacteria among Wild-Caught Phlebotomus argentipes (Psychodidae: Phlebotominae), the Vector of Leishmaniasis in Sri Lanka. - Gunathilaka, Nayana; Perera, Hirunika; Wijerathna, Tharaka; Rodrigo, Wasana; Wijegunawardana, N. D. A. D. (BioMed Research International, 2020)
Phlebotomus argentipes is the main suspected vector for leishmaniasis in Sri Lanka. Investigations on the presence of aerobic bacteria in the gut of sand flies which evidence a potential approach to control leishmaniasis transmission through a paratransgenic strategy are still not available for the local sand fly populations. Field-caught unfed female sand flies collected from three selected Medical Officer of Health (MOH) areas (Polpithigama, Maho, and Galgamuwa) in Kurunegala District, Sri Lanka from August to December 2018 were used. Prokaryotic 16S ribosomal RNA partial gene was amplified and sequenced. Morphological identification revealed the presence of only one sand fly species, P. argentipes (n = 1,969). A total of 20 organisms belonging to two phyla (Proteobactericea and Furmicutes) were detected within the gut microbial community of the studied sand fly specimens. This study documents the first-ever observation of Rhizobium sp. in the midgut of P. argentipes. The presence of Bacillus megaterium, which is considered as a nonpathogenic bacterium with potential use for paratransgenic manipulation of P. argentipes suggest that it may be used as a delivery vehicle to block the vectorial transmission of Leishmania parasites. In addition, Serratia marcescens may be used as a potential candidate to block the parasite development in sand fly vectors since it has evidenced antileishmanial activities in previous investigations. Hence, further studies are required to gain full insight into the potential use of this bacterium in the control of Leishmania parasites through paratransgenesis.